ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN KOPI INSTAN - Fityan Mizfar; Aldon Sinaga (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
Coffee (Coffea sp), has an important role as a significant influence in live and livelihood of majority community as well as foreign exchange earner for state. It is known that coffee is one of flagship products in Indonesian commodities, noted that Indonesia is one of the world's largest coffee exporting nation. Instant coffee which is available at this time has been accepted by community which is caused by two factors.First, manufacturers build consumer perceptions that the products are kind of instant coffee beverage that offers practicality in its presentation, and not leaving a coarse powder  or  residue  when  drunk.  Second,  intelligence  producers  through  advertising, where instant coffee is identical with urban culture, modern society, and people who are always busy with various kinds of work which spends time. The research goal was to  identify  the  factors  influencing  consumer  decision  in  buying  instant  coffee, especially coffee consumers on internet social networking users, by using Quota NonProbabilistic  Sampling.  The  data  analysis  in  this  study  used  multiple  regression analysis. The population was the entire of social networking users both personal and group. The results showed that the factors influencing consumer decisions in buying instant  coffee  were:  sex  (1.555),  duration  of  activity  or  working  hours  (0.933), education  (0.198),  and  information  (0.928).  Sex  factor  (1.555)  was  dominant  to influence  consumer  decisions  in  buying  instant  coffee.  This  occurred  because  there was  psychological  aspect  that  could  pose  great  effects.  It  is  recommended  for entrepreneurs  in  marketing  products  through television  media  to be  more  enhanced because most consumers find out information about coffee through the media. And for further researchers, it is expected to examine other factors that may affect consumers in making decision in buying instant coffee.